Evaluating The Influence Of Satisfaction As A Mediator On Generation Z’s Loyalty To Airline ‘Aa’ - Ruslim, Tommy Setiawan; Soelaiman, Lydiawati; Suryawan, Ian Nurpatria (Media Bisnis, 2025)
Aviation transportation services are something that people really need nowadays to make it easier to move from one place to another. The aviation industry in Indonesia is experiencing a surge in demand from the local community. The importance of customer loyalty in the aviation industry aims to maintain the existence of an airline or is even expected to be able to improve it so that it can become a superior airline in the aviation industry. Generation Z was found to prioritize air transportation as the main thing and factor in traveling. In realizing an optimal domestic airline aviation industry, "AA" implements strategies to realize business growth as an airline amidst the tightness of the industry. Loyalty can be influenced by satisfaction, likewise satisfaction can be influenced by service quality and brand image. This research aims to determine the factors that can influence "AA" airline loyalty in generation Z with satisfaction as a mediating variable.